Genome-wide identification of R-SNARE gene family in upland cotton and function analysis of GhVAMP72l response to drought stress - Li, Bingxuan; Zhou, Gen; Li, Yanbin; Chen, Xueting; Yang, Huiting; Li, Yan; Zhu, Minhua; Li, Libei (Frontiers in Plant Science, 2023)
Soluble N-ethylmaleimide sensitive factor attachment protein receptors (R-SNAREs) was mainly promoted the assembly of SNARE complex to drive the final membrane fusion step of membrane transport. Previous research on R-SNAREs has mainly focused on development and growth, and has rarely involved in abiotic stress, especially in cotton. Here, we performed a comprehensive analysis of R-SNAREs genes in upland cotton. In total, 51 Gh-R-SNARE genes across six phylogenetic groups were unevenly distributed on 21 chromosomes. Moreover, Cis-elements related to plant growth and response to abiotic stress responses were found in the promoter region of Gh-R-SNAREs. Nine Gh-R-SNARE genes was obviously upregulated under drought stress conditions by RNA-seq and qRT-PCR analysis. Among them, GhVAMP72l might be the key candidate gene contributing to drought stress tolerance in cotton by virus-induced gene silencing (VIGS) assay. These results provided valuable insights for the functional analysis of cotton R-SNAREs in response to drought stress and highlight potential beneficial genes for genetic improvement and breeding in cotton.